Correlation Between Maximal Tongue Pressure and Swallowing Function in Spinal and Bulbar Muscular Atrophy - Gwak, Dae-Won; Jung, Seung-Hwan; Min, Yu-Sun; Park, Jin-Sung; Cho, Hee-Jin; Park, Donghwi; Hong, Min Woo; Kang, Min-Gu (Frontiers in Neurology, 2021)
Background: Spinal and bulbar muscular atrophy (SBMA) is an X-lined motor neuron disease characterized by progressive muscle weakness, bulbar palsy, and dysphagia. Dysphagia is associated with tongue weakness, which is a common manifestation of SBMA. This study aimed to investigate the correlations between tongue pressure and dysphagia in patients with SBMA. Materials and Methods: Thirty-nine genetically confirmed SBMA patients underwent a videofluoroscopic swallowing study (VFSS) and tongue pressure assessment. Then, we analyzed the maximal tongue pressure (MTP), oral transit time, penetration-aspiration scale (PAS), videofluoroscopic dysphagia scale (VDS), amyotrophic lateral sclerosis functional rating scale-revised (ALSFRS-R), and 6-minute walk test (6MWT). Pearson and Spearman correlation coefficients were calculated to analyze the association of the MTP with clinical, swallowing, and functional parameters. Results: In the correlation analysis, MTP was negatively correlated with disease duration (r = -0.396, p = 0.013) and VDS (r = -0.426, p = 0.007), and positively correlated with ALSFRS-R (r = 0.483, p = 0.002) and 6MWT (r = 0.396, p = 0.013). The bulbar (r = 0.367, p = 0.022) and gross motor (r = 0.486, p = 0.002) domains of the ALSFRS-R were correlated with MTP. Conclusion: Tongue pressure assessment can be used as a safe and easy tool to assess swallowing function in SBMA patients. Moreover, MTP reflects functional states, including activities of daily living and gait performance, showing it to be a potential biomarker for physical performance in SBMA.